2006
DOI: 10.1111/j.1600-6143.2006.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Donor Chimerism and Inducing Tolerance to Islet Allografts by Post-Transplant Donor Lymphocyte Infusion

Abstract: Inducing donor chimerism is the most consistently successful approach to achieve transplant tolerance. We found that a low level of donor chimerism, which was induced by a relatively non-toxic approach, induced donor-specific tolerance to islet allografts in chemically induced diabetic mice. However, a similar level of donor chimerism could not protect donor islet allografts in non-obese diabetic (NOD) mice that spontaneously developed autoimmune diabetes. Rejection of donor islet allografts in diabetic NOD mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…However, although islet-specific autoimmunity could lead to donor islet rejection by chimeras, as suggested in a previous study (32), the lack of syngeneic islet rejection in our study indicated that autoimmunity could not explain the split tolerance. The remaining low-level alloreactivity to the donor, detected in NOD chimeras, could instead explain their increased split tolerance as compared with B6 chimeras.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…However, although islet-specific autoimmunity could lead to donor islet rejection by chimeras, as suggested in a previous study (32), the lack of syngeneic islet rejection in our study indicated that autoimmunity could not explain the split tolerance. The remaining low-level alloreactivity to the donor, detected in NOD chimeras, could instead explain their increased split tolerance as compared with B6 chimeras.…”
Section: Discussionmentioning
confidence: 44%
“…The strain combinations used in these studies in most cases were not fully mismatched, having either partial (31,32,44,45) or complete MHC matches (46). Difficulty in sustaining mixed chimerism long term was encountered even in studies that used partially matched donor bone marrow (32,44). However, in one study, fully mismatched islets were accepted by diabetic NOD mice made chimeric, although full chimerism may have explained the tolerance (43).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The induction of tolerance to islet antigens via treatment with hematopoietic lineage cells has been reported in a variety of model systems (39)(40)(41). In other model systems, these cell transfers have been thought to result in changes in antigen presentation that preferentially engage tolerance and suppressive mechanisms on APC subsets and naïve and effector T-cell subsets.…”
Section: Discussionmentioning
confidence: 99%